2015
DOI: 10.1186/s12957-015-0678-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and hospital costs following esophageal resection: a prospective cohort study

Abstract: BackgroundThe incidence rates for adenocarcinoma of the esophagus are increasing while the prognosis has only improved slightly. There is no apparent benefit in short- and long-term survival after different surgical strategies, but surgery is associated with significant morbidity. The goal of this study is to prospectively assess the quality of life and hospital costs after esophageal resections depending on the development of complications.MethodsProspective data was collected from 47 patients undergoing an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We found that the expenditure for stage II–III diseases was relatively higher than those for stage I and IV diseases, which seems to be reasonable if we take the differences of both survival and treatment among patients with I–IV diseases into consideration. As we all know, patients with stage I disease were mainly cured by surgery alone, which was relatively cheap, and those with stage IV disease was commonly treated with palliative care and with short survival period, whereas for patients with stage II and III diseases, multidisciplinary treatment were often adopted, which usually contain expensive antitumor drugs [ 20 ]. In addition, in the present study, the proportion of selected patients with stage I disease (7.56%) was lower than the target proportion (25%–30%), even after substantial effort, indicating that most esophageal cancer patients were diagnosed with a late stage disease in the absence of routine esophageal cancer screening or early detection and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expenditure for stage II–III diseases was relatively higher than those for stage I and IV diseases, which seems to be reasonable if we take the differences of both survival and treatment among patients with I–IV diseases into consideration. As we all know, patients with stage I disease were mainly cured by surgery alone, which was relatively cheap, and those with stage IV disease was commonly treated with palliative care and with short survival period, whereas for patients with stage II and III diseases, multidisciplinary treatment were often adopted, which usually contain expensive antitumor drugs [ 20 ]. In addition, in the present study, the proportion of selected patients with stage I disease (7.56%) was lower than the target proportion (25%–30%), even after substantial effort, indicating that most esophageal cancer patients were diagnosed with a late stage disease in the absence of routine esophageal cancer screening or early detection and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Esophagectomy is associated with high postoperative morbidity (Clavien-Dindo grade !3) of 60%, mortality rates up to 5%, and a large impact on quality of life. [2][3][4] After neoadjuvant treatment, a pathological complete response (ypCR) (no viable tumor cells found in the specimen, including in resected lymph nodes) was observed in 24% to 32% of patients. [5][6][7] For the complete responders, active surveillance might have been a safer alternative instead of esophagectomy, and whether secondary surgery in cases of locoregional recurrence might still be a curative option is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…However, symptoms after esophagectomy such as diarrhea, nausea and reflux, can persist up to 10 years after surgery [12]. A study by Strik et al [13] found no difference in HRQoL between individuals suffering from different severity levels of complications.…”
Section: Introductionmentioning
confidence: 99%